Science, Technology, Engineering, and Mathematics Professional Development on Science Learning: A Review - Zuhaida, Anggun; Widodo, Ari; Prima, Eka Cahya; Solihat, Rini (UIN Fatmawati Sukarno Bengkulu, 2024)
The STEM professional development (STEM PD) programs are important in improving teacher competence in developing STEM-integrated science learning. This study aims to determine the progress of STEM PD programs and effective STEM PD programs in science learning. The methodology used in this study is a systematic literature review conducted through 3 main stages: planning, conducting, and reporting the review. The results of the study stated that the progress of the STEM PD program can be seen in teacher participation, changes in teacher competencies, integration of STEM in the curriculum, improved student skills, and resource enhancement. Furthermore, an effective STEM PD program can be seen from the STEM approach, collaboration and partnerships, use of media and technology, stakeholder support, and sustainability. This study concludes that implementing STEM PD in science learning should be carried out sustainably so that teachers will continue to be exposed to the integration of STEM in science learning. STEM PD implemented with commitment and appropriate efforts will improve teacher competence and student interest in STEM-based science learning.